Compound heat transfer enhancement of a dimpled tube with a twisted tape swirl generator - Thianpong, Chinaruk; Eiamsa-ard, Petpices; Wongcharee, Khwanchit; Eiamsa-ard, Smith (My University, 2009)
Friction and compound heat transfer behaviors in a dimpled tube fitted with a twisted tape swirl generator are investigated experimentally using air as working fluid. The effects of the pitch and twist ratio on the average heat transfer coefficient and the pressure loss are determined in a circular tube with the fully developed flow for the Reynolds number in the range of 12,000 to 44,000. The experiments are performed using two dimpled tubes with different pitch ratios of dimpled surfaces (PR = 0.7 and 1.0) and three twisted tapes with three different twist ratios (y/w = 3, 5, and 7). Experiments using plain tube and dimpled tube acting alone are also carried out for comparison. The experimental results reveal that both heat transfer coefficient and friction factor in the dimpled tube fitted with the twisted tape, are higher than those in the dimple tube acting alone and plain tube. It is also found that the heat transfer coefficient and friction factor in the combined devices increase as the pitch ratio (PR) and twist ratio (y/w) decrease. In addition, an empirical correlation based on the experimental results of the present study is sufficiently accurate for prediction the heat transfer (Nu) and friction factor (f) behaviors. © 2009 Elsevier Ltd. All rights reserved.
Keywords: Compound heat transfer; Dimpled tube; Friction factor; Twisted tape